Chapter Introduction - Kustritz, Anne (Taylor & Francis, 2024)
This introduction explains the purpose of this book in documenting and theorizing the slash fan fiction community's transtion from print to digital circulation around the turn of the millenium. Fan fiction describes original stories that borrow characters, settings, and/or situations from existing sources, and slash specifies fan works that construct a same-sex relationship. Written predominantly by women, slash participants have created their own infrastructure for women's creative expression, queer representation, and community space. This book borrows from critical ethnography, literary theory, cultural studies of law, and public sphere theory to analyze the way in which the idea of "slash" functions as a flexible space of multiplicity and possibility.